Perilaku Organisasi terhadap Penurunan Prevalensi Stunting di Kabupaten Buton Tengah - Munawir, Hardianty; Islamy, La Ode Syaiful; Ramadhan, Syahril (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2024)
The reduction in stunting prevalence is a long-term investment that will bring significant benefits to individuals, communities, and the nation. The purpose of this research is to describe organizational behavior toward reducing the prevalence of stunting in Buton Tengah Regency using a descriptive qualitative approach, with informants selected through purposive sampling. The research results show that organizational behavior, including the commitment from policymakers and Regional Apparatus Organizations, has been well-mapped. The Buton Tengah Regency Government has allocated a specific budget as an action to accelerate the reduction of stunting. On the other hand, while coordination between policymakers and relevant Regional Apparatus Organizations has been implemented, there are still obstacles in terms of the availability of an integrated data management system and the inconsistency of some stakeholders in the coordination process.